1995
DOI: 10.1007/bf00179969
|View full text |Cite
|
Sign up to set email alerts
|

Revision surgery for lumbar disc herniation

Abstract: We reviewed 45 patients who had undergone repeated open operations for lumbar disc herniation. There were 26 men and 19 women with a mean follow up of 4.3 years. Twenty-fourpatients had had one previous discectomy, 12 had 2, and 9 had 3 or more; 11 needed a fusion without instrumentation. Residual or re-extruded disc hernias, either sub-or transligamentous, were frequently found at revision. Good to excellent results were obtained in 64%. Those who had a first-time revision had earlier improvement and better r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…4,10,13,19 Microendoscopic discectomy approaches for primary lumbar disc herniation have also yielded comparable success rates, although long-term outcome data are still forthcoming. 1,15 In terms of reoperation for recurrent lumbar disc herniations, open discectomy has resulted in acceptable relief of radicular pain and overall success rates comparable with the primary surgery. 3,7,8,17,18 In general, factors favoring a successful outcome after reoperation for recurrent lumbar disc herniation have included a pain-free interval longer than 6 months after the initial surgery, revision incorporating a fusion, and a definitive finding of a recurrent disc at surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…4,10,13,19 Microendoscopic discectomy approaches for primary lumbar disc herniation have also yielded comparable success rates, although long-term outcome data are still forthcoming. 1,15 In terms of reoperation for recurrent lumbar disc herniations, open discectomy has resulted in acceptable relief of radicular pain and overall success rates comparable with the primary surgery. 3,7,8,17,18 In general, factors favoring a successful outcome after reoperation for recurrent lumbar disc herniation have included a pain-free interval longer than 6 months after the initial surgery, revision incorporating a fusion, and a definitive finding of a recurrent disc at surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, cases of failed-back syndrome requiring revision discectomy and fusion can also be treated using minimal-access techniques. In a study of 45 patients treated for single or multiple recurrent disc herniation, of which 24% required concurrent fusion, Baba, et al, 1 concluded that minimal destruction of the posterior elements was crucial for improving outcomes in revision lumbar surgery. Minimal-access techniques are ideally suited for reducing destruction of posterior elements, which includes muscle, ligaments, and bone.…”
Section: Discussionmentioning
confidence: 98%
“…[13] Although early reports documented less satisfactory outcomes with revision discectomy,[1314] more investigations which controlled for confounding factors such as foraminal stenosis and adjacent level herniations showed that results are more comparable with those for primary disc surgery. [12378910] Cinotti et al .…”
Section: Discussionmentioning
confidence: 99%
“…However Baba and his friends Express that anulus and nucleus have to been removed as much as possible (20). It is also stated that radical discectomy decreases disc function and lead patients experience postoperative back pain more (19).…”
Section: Resultsmentioning
confidence: 99%